2020
DOI: 10.18203/2349-3291.ijcp20204542
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of pediatric renal diseases in a rural tertiary care hospital

Abstract: Background: Spectrum of renal disease varies in different population, geographical location, and by environmental factors. The purpose of this study was to find out the occurrence of different pediatric renal diseases at a teaching hospital in the rural part of Maharashtra, India.Methods: All cases of renal diseases from one month to 12 years of age, admitted to the wards during the period of July 2018 to December 2019, were included in the study. Detailed clinical and laboratory evaluations were performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
2
5
1
Order By: Relevance
“…We documented an incidence of 2.2% (22 renal cases per 1000 children seen) for kidney disease among paediatric hospital admissions over a period of 8 months. It was comparable with studies in India, 9 however lower incidence rate of 1.1% have been reported in South Nigeria 21 and high rate of 6.3% was documented in Nepal. 22 Burden of kidney disease differs among different countries due to differences in genetic predisposition, environmental factors, clinical and laboratory capacities to diagnose kidney diseases.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We documented an incidence of 2.2% (22 renal cases per 1000 children seen) for kidney disease among paediatric hospital admissions over a period of 8 months. It was comparable with studies in India, 9 however lower incidence rate of 1.1% have been reported in South Nigeria 21 and high rate of 6.3% was documented in Nepal. 22 Burden of kidney disease differs among different countries due to differences in genetic predisposition, environmental factors, clinical and laboratory capacities to diagnose kidney diseases.…”
Section: Discussionsupporting
confidence: 89%
“…Mean(SD) age of presentation in our study was 5.5 ± 3.5 years with a M:F ratio of 1.5:1 and most children were aged between 0 and 5 years as seen in other studies. 9,23 As shown in other studies in Africa 6 and Bangladesh 23 the most common kidney diseases requiring admission in the unit were AKI, ESKD and nephrotic syndrome. Unlike in India, 24 another developing economy, where post infectious glomerulonephritis is still constituting a majority of admissions, our unit only encountered 5 children (10%) with this condition.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Nine (24.3%) children who were diagnosed with UTI were associated with other renal diseases like AGN, CAKUT, AKI and CKD. Similarly, other studies have also reported occurrences of UTI in association with the above mentioned renal disorders 4,21,23 . E. coli (61.4%) was the commonest cause of culture-positive UTI, which was similar to many reviews of renal diseases in children from other parts of the world like Nepal, Iraq and the Kingdom of Saudi Arabia 1,3,9 .…”
Section: Discussionsupporting
confidence: 62%
“…There are primary and secondary disorders that can lead to glomerular diseases [1]. The variations regarding the pattern of renal diseases among the pediatrics are possibly related to differences in environmental risk factors for renal diseases, genetic predisposition, and the clinical and laboratory capacities in the diagnosis [2].…”
Section: Introductionmentioning
confidence: 99%